Epigenetic and Metabolic Changes in Diffuse Intrinsic Pontine Glioma - Park, Jiyoon; Chung, Chan (Brain tumor research and treatment, 2023)
Diffuse midline glioma (DMG), hitherto known as diffuse intrinsic pontine glioma (DIPG), is a rare and aggressive form of brain cancer that primarily affects children. Although the exact cause of DMG/DIPG is not known, a large proportion of DMG/DIPG tumors harbor mutations in the gene encoding the histone H3 protein, specifically the H3K27M mutation. This mutation decreases the level of H3K27me3, a histone modification that plays a vital role in regulating gene expression through epigenetic regulation. The mutation also alters the function of polycomb repressive complex 2 (PRC2), thereby preventing the repression of genes associated with cancer development. The decrease in H3K27me3 caused by the histone H3 mutation is accompanied by an increase in the level of H3K27ac, a post-translational modification related to active transcription. Dysregulation of histone modification markedly affects gene expression, contributing to cancer development and progression by promoting uncontrolled cell proliferation, tumor growth, and metabolism. DMG/DIPG alters the metabolism of methionine and the tricarboxylic acid cycle, as well as glucose and glutamine uptake. The role of epigenetic and metabolic changes in the development of DMG/DIPG has been studied extensively, and understanding these changes is critical to developing therapies targeting these pathways. Studies are currently underway to identify new therapeutic targets for DMG/DIPG, which may lead to the development of effective treatments for this devastating disease.